Neoadjuvant paclitaxel/olaparib in comparison to paclitaxel/carboplatinum in patients with HER2-negative breast cancer and homologous recombination deficiency (GeparOLA study) - Fasching, Peter Andreas; Link, T.; Hauke, J.; Seither, F.; Jackisch, C.; Klare, P.; Schmatloch, S.; Hanusch, C.; Huober, J.; Stefek, A.; Seiler, S.; Schmitt, W. D.; et al. (Annals of oncology, 2021)
Background - The efficacy and toxicity of olaparib as combination therapy in early breast cancer (BC) patients with homologous recombinant deficiency (HRD) [score high and/or germline (g) or tumour (t) BRCA1/2 mutation] is not well described. GeparOLA (ClinicalTrials.gov, NCT02789332) investigated olaparib in combination with paclitaxel in HER2-negative early BC with HRD. - Patients and methods - Patients with untreated primary HER2-negative cT2-cT4a-d or cT1c with either cN+ or pNSLN+ or cT1c and triple-negative breast cancer (TNBC) or cT1c and Ki-67>20% BC with HRD were randomised either to paclitaxel (P) 80 mg/m2 weekly plus olaparib (O) 100 mg twice daily for 12 weeks or P plus carboplatinum (Cb) area under the curve 2 weekly for 12 weeks, both followed by epirubicin/cyclophosphamide (EC). Stratification factors were hormone receptor (HR) status (HR+ versus HR−) and age (<40 versus ≥40 years). The primary endpoint was pathological complete response (pCR; ypT0/is ypN0). A two-sided one-group χ2-test was planned to exclude a pCR rate of ≤55% in the PO-EC arm. Secondary end points were other pCR definitions, breast conservation rate, clinical/imaging response, tolerability and safety. - Results - A total of 107 patients were randomised between September 2016 and July 2018; 106 (PO N = 69; PCb N = 37) started treatment. Median age was 47.0 years (range 25.0-71.0); 36.2% had cT1, 61.0% cT2, 2.9% cT3, and 31.8% cN-positive tumours; grade 3 tumours: 86.8%; Ki-67>20%: 89.6%; TNBC: 72.6%; confirmed gBRCA1/2 mutation: 56.2%. The pCR rate with PO was 55.1% [90% confidence interval (CI) 44.5% to 65.3%] versus PCb 48.6% (90% CI 34.3% to 63.2%). Analysis for the stratified subgroups showed higher pCR rates with PO in the cohorts of patients <40 years and HR+ patients. - Conclusion - GeparOLA could not exclude a pCR rate of ≤55% in the PO arm. PO was significantly better tolerated and the combination merits further evaluation.
Available online: 21 October 2020
Gesehen am 15.02.2021